2021
DOI: 10.1017/s0007114521002786
|View full text |Cite
|
Sign up to set email alerts
|

Maternal dietary intake, nutritional status and macronutrient composition of human breast milk: systematic review

Abstract: Introduction: Human breast milk is the best source of nutrition in early life, particularly during the first six months. Nevertheless, human breast milk composition is variable and more insight in the exact factors contributing to this variability is warranted. In this review, we explored the impact of maternal dietary intake and nutritional status (e.g., anthropometric measures, body mass index, bioimpedance) on human milk macronutrient composition. Method: PubMed, Scopus and Cochrane w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 79 publications
(440 reference statements)
0
7
0
1
Order By: Relevance
“…Apart from methodological factors, human milk is known to be influenced by maternal nutritional status, dietary intake, socioeconomic status, and regional variations [ 23 , 35 , 39 , 40 , 41 , 50 , 96 ]. In this review, four studies objectively compared different maternal BMI categories and its potential impact on milk composition [ 58 , 83 , 88 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Apart from methodological factors, human milk is known to be influenced by maternal nutritional status, dietary intake, socioeconomic status, and regional variations [ 23 , 35 , 39 , 40 , 41 , 50 , 96 ]. In this review, four studies objectively compared different maternal BMI categories and its potential impact on milk composition [ 58 , 83 , 88 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, basis this review, we observe there may be a mild association of maternal BMI on milk protein (specially in colostrum), but needs to be further confirmed as data on maternal BMI and milk protein composition was limited. A recent review reported mixed results for maternal BMI and milk protein with almost 58% of the studies citing no association [ 41 ]. Similarly, another review reported protein concentration in breast milk was comparable between overweight and normal weight women in different stages of lactation [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Countries with high food deficits coincide with parts of the world with large fat gaps: Eastern, Northern, Middle and Western Africa; East, Southeast and South Asia, and the Caribbean ( 5 ). Understanding fats in diets of undernourished people is important, and may also impact infants through quality of breast milk related to fat intake by mothers ( 30 ). Regional studies in South America note, however, that feeding energy-rich micronutrient-poor foods to undernourished people can promote obesity ( 31 ).…”
Section: Affordable Fats Of Satisfactory Nutritional Valuementioning
confidence: 99%